Mary Astell’s “Machiavellian Moment” in Moderation truly Stated - Guerrero, Leandro (Locke Studies, 2025)
In this paper I focus on Mary Astell’s treatment and uses of Machiavelli’s works and ideas in her political pamphlet Moderation truly Stated. I claim that there is in it an Anglican appropriation of some Machiavellian civic-humanist vocabulary. I show that in reconciling key Machiavellian insights with her Christian view of politics, Astell considerably qualifies them. Nevertheless, I argue that they are indeed operative in her political arguments (explicitly and implicitly), most significantly in its feminist agenda. I conclude, against some previous interpretations, that there is a neo-Machiavellian side to Astellian political analysis, both at the theoretical and pragmatic level.